Emerging Issues due to Adoption of Submersible Pump Technology in Marginal Quality Areas of Haryana - Kaledhonkar, M. J.; Gupta, S. K.; Saxena, C. K.; Sharma, D. P.; Kumar, Ashwani (Journal of Agricultural Engineering, 2014)
Declining water table, indicative of overall negative ground water balance, has emerged as the most serious challenge to sustainability of irrigated agriculture in many states of India. It is resulting in reduced discharge from shallow wells, and replacement of centrifugal with submersible pumps. It is more so in marginal ground water quality areas such as Assandh block of Karnal district of Haryana, where deep semi-confined aquifers are of relatively good quality as compared to shallow aquifers. Ground water balance of the Assandh block, a marginal water quality area, was assessed based on the net annual pumping from the groundwater and net annual replenishable recharge. Even under the existing set-up, net annual replenishable recharge was negative and would result in lowering of water table by 80-90 cm.annum-1. Temporal changes in pumped water quality revealed some increase in EC of the water of deeper aquifer. Studies revealed that water productivity was low under submersible than under centrifugal pump systems, mainly due to higher water application under the former situation. Under both the situations, pump efficiencies for selected centrifugal and submersible pumps were low (< 40%), although relatively higher efficiencies were observed for submersible pumps. Inappropriate size of submersible pumps and its placement at inappropriate depth were few reasons of low efficiencies amongst others. Since rice-wheat crop rotation is being factored as the major cause of groundwater decline in several states, notably Haryana, Punjab and Western Uttar Pradesh, diversification to low water requiring crops would help halt the declining trend in the water table to some extent, and would reduce the replacement rate of centrifugal to submersible pumps.